Physiological and Proteomic Analysis Responsive Mechanisms for Salt Stress in Oat - Chen, Xiaojing; Xu, Zhongshan; Zhao, Baoping; Yang, Yanming; Mi, Junzhen; Zhao, Zhou; Liu, Jinghui (Frontiers in Plant Science, 2022)
Oat is considered as a moderately salt-tolerant crop that can be used to improve saline and alkaline soils. Previous studies have focused on short-term salt stress exposure, and the molecular mechanisms of salt tolerance in oat have not yet been elucidated. In this study, the salt-tolerant oat cultivar Vao-9 and the salt-sensitive oat cultivar Bai5 were treated with 6 days of 0 and 150 mmol L−1 salt stress (nNaCl:nNa2SO4 = 1:1). Label-Free technology was then used to analyze the differentially expressed proteins in leaves under 0 and 150 mmol L−1 salt stress. The obtained results indicated that total of 2,631 proteins were identified by mass spectrometry in the four samples. The salt-tolerant cultivar Vao-9 mainly enhances its carbohydrate and energy metabolism through the pentose and glucuronate interconversions, and carbon fixation pathways in prokaryotes, thereby reducing the damage caused by salt stress. In addition, the down-regulation of ribosomes expression and the up-regulated expression of HSPs and CRT are all through the regulation of protein synthesis in response to salt stress. However, GABA metabolism presents a different synthesis pattern in Bai5 and Vao-9. The main KEGG function of differential expressed protein (DEP) in Bai5 is classified into protein processing in the endoplasmic reticulum, estrogen signaling pathway, antigen processing and presentation, longevity regulating pathway-multiple species, arginine and proline metabolism, beta-alanine metabolism, vitamin B6 metabolism, salmonella infection, chloroalkane and chloroalkene degradation, and limonene and pinene degradation. Moreover, the main KEGG functions of DEP in Vao-9 are classified as ribosome and carbon fixation pathways in prokaryotes, pentose and glucuronate interconversions, GABA ergic synapse, and taurine and hypotaurine metabolism. The results obtained in this study provide an important basis for further research on the underlying mechanisms of salt response and tolerance in oat and other plant species.